Menopausal Status as the Strongest Independent Predictor of Neoadjuvant Chemotherapy Response in Locally Advanced Breast Cancer - Stephen William Soeseno; I Wayan Sudarsa; Ni Gusti Ayu Agung Manik Yuniawaty Wetan (HM Publisher, 2026)
Background: Neoadjuvant chemotherapy (NAC) is the standard treatment for locally advanced breast cancer (LABC), yet predicting individual patient response remains challenging. This study investigates menopausal status and other clinicopathological factors as predictors of NAC response in a Southeast Asian population. Methods: This retrospective cohort study analyzed 247 LABC patients treated with NAC between 2022–2023 at the Oncology Surgery Division, Prof. Dr. I.G.N.G. Ngoerah General Hospital, Denpasar, Bali. Variables included menopausal status (premenopausal vs. postmenopausal), histological type, histological grading, molecular subtype, lymphovascular invasion (LVI), tumor-infiltrating lymphocytes (TIL), and age. Bivariate analysis used chi-square tests; multivariate logistic regression identified independent predictors. Results: Among 247 patients (mean age 51.7 ± 9.1 years), 130 (52.6%) achieved positive response. Postmenopausal patients demonstrated significantly higher response rates (79.7% vs. 12.1%, p<0.001). Multivariate analysis revealed menopausal status as the strongest predictor (OR=14.999, 95%CI: 6.045–37.213, p<0.001), followed by molecular subtype (OR=4.182, p=0.006), histological grading (OR=3.596, p=0.010), and histological type (OR=0.367, p=0.017). Age, LVI, and TIL lost statistical significance in the multivariate model. Conclusion: Menopausal status emerged as the strongest independent predictor of NAC response in LABC, suggesting that hormonal factors play a pivotal role in chemotherapy sensitivity. These findings support more aggressive NAC regimens or combined endocrine-cytotoxic strategies for postmenopausal patients and warrant validation in prospective Southeast Asian cohorts.